Q: What is x2 times 3x2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 + x2 + x2 = (1 + 1 + 1)x2 = 3x2

2x2 + x2 = 3x2

Assuming the 2 is meant to be a square this is the form: x2 - 3x2 = -2x2 + 8x + 5

x2 - (2x)2 = x2 - 4x2 = -3x2 x2 - 2x2 = -x2

3x2(x2 - 3)

Related questions

I am assuming that in this question x2 refers to x2 since otherwise the second term "x2" makes no sense. Then 3x2/x2 = 3.

It means times 2. As in 3X2 means three times two, which is six.

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)

x2 + x2 + x2 = (1 + 1 + 1)x2 = 3x2

2x2 + x2 = 3x2

Assuming the 2 is meant to be a square this is the form: x2 - 3x2 = -2x2 + 8x + 5

x2 - (2x)2 = x2 - 4x2 = -3x2 x2 - 2x2 = -x2

(3x4 + 2x3 - x2 - x - 6)/(x2 + 1)= 3x2 + 2x - 4 + (-3x - 2)/(x2 + 1)= 3x2 + 2x - 4 - (3x + 2)/(x2 + 1)where the quotient is 3x2 + 2x - 4 and the remainder is -(3x + 2).

3x3 - x2 - x - 1 = 3x3 - 3x2 + 2x2 - 2x + x - 1 = 3x2(x - 1) + 2x(x - 1) + 1(x - 1) = (3x2 + 2x + 1)(x - 1) So 3x3 - x2 - x - 1 /(x - 1) = (3x2 + 2x + 1)

I guess that should be 3 times (x squared) minus 48: 3x2 - 48 = 3(x2 - 16) = 3(x + 4)(x - 4)

In general, no.

3x2